PeerA : An App for Online Peer Assessment in Medical Problem-Based Learning Groups - William Lim, Kiong Seng (2024)
Problem-based learning (PBL) in medical curricula nurtures problem-solving, critical thinking and teamwork. PBL groups biweekly over 6-9 weeks per modular Block, addressing weekly problems through self-directed learning and group elaboration. While assessment of PBL can be by self, peer or facilitator, our school practices facilitator grading. This grading had been observed to be non-uniform across groups. Peer evaluation is a professional skill found to improve student performance. We aimed to study the students’ acceptance of peer assessment with a trial using a specially developed app, PeerA. It is designed for confidential weekly grading of peers with formative feedback in the final week of grading. A trial was done with the Year One class of 158 students in one 7-week Block, followed by an online survey. With a response rate of 89% the results showed that 65.3% either agreed or strongly agreed that peer assessment using the app should be implemented in the curriculum. One third of the respondents were neutral to the proposal. Furthermore, 65.3% suggested that peer assessment should contribute at least 50% of PBL grades, with 9.9%% preferring maintaining facilitator assessment. A majority (94.3%) agreed to the current format of weekly app-based grading followed by feedback in the final week. These results show that weekly peer assessment using the PeerA app is accepted by the majority of the students as an alternative evaluation for PBL.